PENGARUH PENERAPAN UNIT LAYANAN PENGADAAN (ULP) TERHADAP EFISIENSI DAN EFEKTIFITAS PENGADAAN BARANG/JASA PADA PEMERINTAH PROPINSI PAPUA - Novijanti A. R. Temaluru; Meinarni Asnawi; Syaikhul Falah (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2016)
The objective of this research was to assess and analyse the effect of duties and responsibilities to efficiency and effectiveness of budgets in Procurement Service Units (PSU). The number of research population in this study was 161 participants of whom were the employees of the formed Team Work. A purposive sampling technique was employed to determine that the 50 respondents selected. Data collections were conducted through direct survey. To test research hypotheses, a multiple regression was applied to find empirical results. The results showed that in partial the PSU positively associated with efficiency and effectiveness of budgets in Papua province. This inferred that the first hypothesis was supported. Furthermore, the responsibilities of PSU significantly associated with the level of efficiency and effectiveness of budgets in Papua province. Hence, the second hypothesis was supported. This study was also revealed that duties and responsibilities simultaneously associated with the level of efficiency and effectiveness of budgets in Papua province. Key words: Duties, Responsibilities, Efficiency and Effectiveness of Budgets